2017
DOI: 10.1159/000479979
|View full text |Cite
|
Sign up to set email alerts
|

Human Antibody Fusion Proteins/Antibody Drug Conjugates in Breast and Ovarian Cancer

Abstract: Considerable research efforts have been dedicated to understanding ovarian and breast cancer mechanisms, but there has been little progress translating the research into effective clinical applications. Hence, personalized/precision medicine has emerged because of its potential to improve the accuracy of tumor targeting and minimize toxicity to normal tissue. Targeted therapy in both breast and ovarian cancer has focused on antibodies, antibody drug conjugates (ADCs), and very recently the introduction of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 101 publications
(183 reference statements)
0
14
0
Order By: Relevance
“…Our results demonstrated that the fusion proteins enabled targeted delivery of siRNA which was internalized into PSMA+ prostate cancer cells 25. Although, the anti-PSMA scFv-based siRNA delivery platform exhibited several advantages compared to nanoparticles, lipid spheres, or even an exosomal siRNA delivery system, it still had some unavoidable drawbacks, such as easy availability, potential immunogenicity, rapid renal clearance, short circulation half-life, and failure in activating complement system-mediated cellular immunity 26, 27. To overcome these obstacles in the clinical application of siRNA delivery systems, we adopted a fast and reliable method first described by BĂ€umer et.al 20, 28 and established stable and efficient transfer carriers for siRNA by PSMA dependent, human monoclonal antibody-mediated delivery platform.…”
Section: Discussionmentioning
confidence: 91%
“…Our results demonstrated that the fusion proteins enabled targeted delivery of siRNA which was internalized into PSMA+ prostate cancer cells 25. Although, the anti-PSMA scFv-based siRNA delivery platform exhibited several advantages compared to nanoparticles, lipid spheres, or even an exosomal siRNA delivery system, it still had some unavoidable drawbacks, such as easy availability, potential immunogenicity, rapid renal clearance, short circulation half-life, and failure in activating complement system-mediated cellular immunity 26, 27. To overcome these obstacles in the clinical application of siRNA delivery systems, we adopted a fast and reliable method first described by BĂ€umer et.al 20, 28 and established stable and efficient transfer carriers for siRNA by PSMA dependent, human monoclonal antibody-mediated delivery platform.…”
Section: Discussionmentioning
confidence: 91%
“…Antibody-drug conjugates (ADCs) are constructed by covalently attaching small-molecule toxins to antibodies (85)(86)(87). T-DM1 is a ADCs that has shown significant activity in treating HER2 + BC (86,87).…”
Section: Her2 Tk Inhibitorsmentioning
confidence: 99%
“…T-DM1 is a ADCs that has shown significant activity in treating HER2 + BC (86,87). A new biparatopic ADC was constructed, consisting of the trastuzumab scFv unit, the 39S Fv unit, and AZ13599185, which inhibits microtubule polymerization during mitosis.…”
Section: Her2 Tk Inhibitorsmentioning
confidence: 99%
“…Koch and Tesar [5] review the concept of bispecific antibodies as effector cell engagers and discuss promising settings for optimal clinical application. Finally, Padayachee and colleagues [6] discuss the potential of antibody drug conjugates and corresponding recombinant antibody fusion proteins in the background of breast cancer.…”
Section: Figmentioning
confidence: 99%